Single-phase distributed generations for power balanced using adaptive real coded genetic algorithm - Umar, Umar; Faanzir, Faanzir; Iswan, Iswan; Rasyid, Ramly; Rahman, Muhammad Natsir; Khairan, Amal; Haryati, Haryati (Institute of Advanced Engineering and Science, 2024)
Easy access to distributed generation (DG) technology is promoting the utilization of single-phase DGs for residential purposes. Surplus energy generated by household DGs can be shared or sold to other communities through existing networks. However, the interconnection of single-phase DGs from residential generators to the distribution network requires careful handling to secure the reliability and quality of the electric power system. This paper focuses on the optimal placement of single-phase multi-type DGs on unbalanced distribution systems that are connected to nonlinear loads. The objective of this study is to minimize the power losses and voltage unbalances in the distribution networks. To verify the efficacy of this method in reducing voltage unbalances and harmonics, an optimization approach is also presented using three-phase DG. Optimal placement of DG is performed on a modified Kaliasin distribution system using an adaptive real coded genetic algorithm (ARC-GA). Simulation results demonstrate that the installation of single-phase DGs is highly effective in reducing power losses and voltage unbalances in the distribution networks.